Solve the system by substitution

-5x-2y= 14

2x4y= -12

### Want to see the full answer?

Check out a sample Q&A here*star_border*

## Related Algebra Q&A

Find answers to questions asked by students like you.

Q: Solve the system by substitution. -2x - 5y 3 3x + 8y=-6

A: Click to see the answer

Q: Solve the system by substitution -3x+4y= -1 4x+8y= -12

A: We have equations :-3x+4y= -1, 4x+8y= -12.Let us isolate equation (2) for x first.Dividing equation…

Q: Solve the system by substitution. -3x + 3y = -36

A: Given:-y=x-3x+3y=-36To solve using substitution

Q: Solve the system by substitution. y = 3x - 50 y = -2x

A: Click to see the answer

Q: Solve the system by substitution. 5x + 4y= -14 y = -7x - 15 (-2, -1)

A: Click to see the answer

Q: Solve the system by substitution. 2x =y- 10 2x +7=2y

A: By solving both equations we get desired resul

Q: Solve the system by substitution> 4x-y=-8 2y-x=9

A: First of all, get the value of “y” in terms of “x” in equation (1) to get equation (3).

Q: Solve the system by substitution. y = -6x -2x – y = 16

A: We have the following equations to be solved using substitution- y = -6x..........(1) -2x - y =…

Q: Solve the system by substitution {-3x+4y=5 {4x-8y=-4

A: From -3x+4y=5 we solve for y.

*question_answer*

Q: Solve the system by substitution: 5x-2y =-7 -4x+ y= 8

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. y=-2x+3 2x+3y=-11

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. y = 10x 7x + 3y = -37

A: y = 10x ...............(1) 7x +3y = -37.............(2) Substituting equation 1 into equation 2;…

*question_answer*

Q: Solve the system by substitution -x-y= 0.1 -3x+6y= 4.8

A: Given, -x-y= 0.1 (i) -3x+6y= 4.8 (ii)

*question_answer*

Q: Solve the system by substitution. = 4y – 6 -4x + 3y = -28

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. Y = -10x + 9 2x – 10y = 12 -

A: Given system of equations are y=-10x+9 .....(1) And 2x-10y=12…

*question_answer*

Q: Solve the system by substitution. y = 7x 45 - y = 2x

A: The given equations are: y=7x-45 and y=2x Let, y=7x-45 -1y=2x -2

*question_answer*

Q: Solve the system by elimination. -4x 3y -27 – 12x + 4y -16

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. -x + 3y = 15 y = 2x

A: To solve the system by substitution -x+3y=15 y=2x

*question_answer*

Q: Solve the system by substitution. y = 4x + 22 %3D y = -7x

A: Solve the system by substitution method y=4x+22 and y=-7x

*question_answer*

Q: Solve the system by substitution. -6x +y= -50 y = -4x

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. {-x-y-z=-8 {-4x+4y+5z=7 {2x+2z=4

A: See the details solution in below

*question_answer*

Q: Solve the system by substitution. 10x – 2y = -16 y = 3x Submit Answer

A: To find the values of x and y by using substitution

*question_answer*

Q: Solve the system by the addition method. 2x + 3y - 11 = 0 3x? - 5y? - 7 = 0

A: 2 x2 + 3 y2 - 11 = 0 3 x2 - 5 y2 - 7 = 0 To Find: x and y using addition method Proof: 2 x2 + 3…

*question_answer*

Q: Solve the system by substitution. 10x + 5y = -–50 Y = -x Submit Answer

A: The given equation is, 10x+5y=-50 y=-x

*question_answer*

Q: Solve the system by substitution. y = 2x y = 10x – 16

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. -6x 8y = 50 - x = -3y Submit Answer

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. y = 5x - 24 y = -3z Submit Answer

A: Given: y=5x-24 ...iy=-3x ...ii

*question_answer*

Q: Solve the system by substitution. -y = x -3x + 3y = -36 Submit Answer

A: -y = x -3x+3y= -36

*question_answer*

Q: Solve the system by substitution. x+7y=-38 7x + 7y = -14

A: Click to see the answer

*question_answer*

Q: Solve the system of equations by substitution. y = -x - 3 y = -2

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. Y = 5x y = 9x + 8

A: Given Data: Equation 1: y=5x Equation 2: y=9x+8 Using the substitution method, Substitute 5x for y…

*question_answer*

Q: Solve the system by substitution. y= x 9x 2y = -49 Submit Answer

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. y = 3x + 28 y = -4x Submit Answer

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. 8x + 9y = -28 -4x = y Submit Answer

A: Answer

*question_answer*

Q: Solve the system by substitution. -7x - 10y = 40 -2y Submit Answer

A: Given system of linear equation -7x -10y = 40 x = -2y

*question_answer*

Q: Solve the system by substitution. -x – y – z = -8 -4x + 4y + 5z = 7 2x + 2z = 4

A: Click to see the answer

*question_answer*

Q: Solve the system by substitution. y = 10x 7x +3y = -37 Submit Answer atter

A: Click to see the answer

*question_answer*

Q: Solve the system by the method of your choice. 3x? + 2y? = 30 2x - 5y? = - 37

A: Solve the system by the substitution method

*question_answer*

Q: Solve the system by substitution. 8x + y = 4 -2x – 8 = y

A: Given the system of equation : 8x + y = 4 1-2x -8 = y 2 By Substitution Method,…

*question_answer*

Q: Solve the system by substitution. y = -6x y = –4x +4 Submit Answer

A: Click to see the answer

*question_answer*

Q: Solve the system by equation -3x+4y= -1 4x+8y= -12

A: Given,

*question_answer*

Q: Solve the system by substitution. y = -4x y = 3x + 28 Submit Answer

A: Given: Two equations: y=-4x ---(1)y=3x+28 ---(2) Substitute equation (1) (y=-4x) in equation (2):…

*question_answer*

Q: Solve the system of equation by elimination. 6x – y = 23 8x + 3y =-9

A: Given, 6x -y = 23 8x +3y = -9 We have to solve given system of equation by elimination.

*question_answer*

Q: solve the system of equations by substitution method 7x-3y = -10 x+3y=2

A: 7x-3y=-10.............(1) x+3y=2 =>x=2-3y.............(2)

*question_answer*

Q: Solve the following system of equations. Enter your answer as an ordered pair. -2z + y = - 17 -3z +…

A: The system of equations,-2x+y=-17-3x+2y=-26

*question_answer*

Q: ) Solve the system by any method: 6x - 3y = 2 - 4x + 5y = - 3 - %3D (Write your answer as an ordered…

A: Click to see the answer

*question_answer*

Q: Solve the system of equations using elimination -5x - 5y = -20 -x -2y =1

A: 0ur Aim is to solve the system of equation given below:--5x-5y=-20 -(i)and -x-2y=1 -(ii), using…

*question_answer*

Q: Solve the system of equations using the addition method. 5x-4y=-6 7x-4y=-2

A: Here, 5x-4y=-6 ……(1) 7x-4y=-2 …….(2)

*question_answer*

Q: Solve this system of equation by substitution y=-3x+5 5x-4y=-3

A: Given: The system of equation is: y=-3x+55x-4y=-3 We have to solve the system by substitution…

*question_answer*

Q: Solve the system by substitution. {−4.5x−2y=−12.5 3.25x−y=−0.75

A: Solve simultaneous linear equation